Association between the pathogenesis and development of sepsis and TIM gene family - YUAN Lingling, DU Xianrong, FENG Jianhong (Zhongguo linchuang yanjiu)
Sepsis is a life-threatening organ dysfunction caused by a series of uncontrolled reactions of the host to infection, trauma, and other factors. In recent years, research has found that various pathological and physiological changes such as inflammation, immune dysfunction, cell apoptosis, autophagy, and coagulation dysfunction are involved in the occurrence and development of sepsis. The proteins encoded by T cell immunoglobulin mucin (TIM) may be potential targets for early diagnosis, immunotherapy, and prognostic evaluation of sepsis. This article provides an overview of the pathogenesis of sepsis and its association with the mucin gene family, in order to provide new ideas for the diagnosis and treatment of sepsis.